PENGEMBANGAN MEDIA PEMBELAJARAN DIOSIR (DIORAMA SIKLUS AIR) UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA SISWA KELAS V SDN DUREN JAYA XIV - Hida Ria Regita; Awalina Barokah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low level of students' understanding of the concept of water cycle material can be influenced by the lack of innovation in the use of learning media. There is a need for media in the form of a water cycle diorama that presents learning materials through interesting illustrations in the learning process. This research aims to develop DIOSIR media (water cycle diorama) and improve students' understanding of the concept. This research uses the Research and Development (R&D) method with the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The feasibility test was carried out by three experts, namely media experts, linguists, and material experts. The media practicality test was carried out using the educator's response, and the media use interest test was carried out using the student's response. The effectiveness test was carried out using pre-test and post-test for grade V students. The results of the study showed that the DIOSIR learning media (water cycle diorama) was declared "very feasible" to use, with evidence of media validation results with a percentage score of 78.1%, linguists 100%, and material 94%. DIOSIR learning media (water cycle diorama) was declared "very practical and interesting" with evidence of the results of the questionnaire responses of educators and students, the results of the educators' responses obtained a percentage value of 92.7% and the responses of students with small group trials obtained a percentage value of 98.2% and large group trials obtained a percentage value of 98.1% and DIOSIR learning media (water cycle diorama) was declared "effective" as evidenced by the results of pre-test and post-test Students, the results of the effectiveness showed a figure of 0.76 proving that "there was a high increase". It can be concluded that comic books as a science learning medium can increase students' understanding of concepts in grade V of SDN Duren Jaya XIV.